2019
DOI: 10.1002/adma.201807267
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Conversion of Alcohols into Bulky Nanoporous Graphene and Pure Hydrogen with Robust Selectivity on CaO

Abstract: The direct conversion of biorenewable alcohols into value‐added graphene and pure hydrogen (H2) at benign conditions is an important challenge, especially, considering the open carbon‐reduced cycle. In this study, it is demonstrated that inexpensive calcium oxide (CaO, from eggshells) can transform alcohols into bulky nanoporous graphene and pure hydrogen (≈99%) with robust selectivity at the temperature as low as 500 °C. Consequently, the growth of graphene can follow the direction of alcohol flow and uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Ethanol produced from the conversion of abundant biomass resources such as low-cost non-edible lignocelluloses, is currently contributing for more than 100 billion litres of fuel to the global energy market in an effort to build a more sustainable future [1][2][3]. Due to its notable advantages including renewability, low toxicity, affordability, ease of storage and high hydrogen content, ethanol has also emerged as a promising feedstock to produce highervalue and cleaner energy carrier, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol produced from the conversion of abundant biomass resources such as low-cost non-edible lignocelluloses, is currently contributing for more than 100 billion litres of fuel to the global energy market in an effort to build a more sustainable future [1][2][3]. Due to its notable advantages including renewability, low toxicity, affordability, ease of storage and high hydrogen content, ethanol has also emerged as a promising feedstock to produce highervalue and cleaner energy carrier, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During CVD reaction, both eggshell and CaCO3 are decomposed into CaO (Fig. S5 in the ESM), which supports the growth of graphene [30]. Intriguingly, HENC tends to grow vertically on CaO and expose ample edge-defective sites for nitrogen doping (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Various oxides have the ability to act as substrates for growing few-layer graphitic or graphene under CVD conditions, such as MgO, 81 ZnO, 82 CaO, [83][84][85] SiO 2 , [86][87][88][89][90] and so forth. The oxides can prompt the decomposition of the carbon source and the deposition of graphitic carbon on their surface.…”
Section: Cvd On Oxide Templates For 3dgmentioning
confidence: 99%
“…CaO is a low‐cost oxide, which is extracted from Ca(OH) 2 , 83 seashells, 84 eggshells, 85 and so forth. Tang et al 83 reported a CaO‐templated growth of hierarchical porous graphene.…”
Section: Synthesis Of 3d Graphene Porous Monolithsmentioning
confidence: 99%
See 1 more Smart Citation